The Relationship Of Lead (Pb) Levels With The Number Of Blood Platelets At SPBU Officers : Hubungan Kadar Timbal (Pb) Dengan Jumlah Trombosit Darah Pada Petugas SPBU - Putri, Mardiana Prasetyani; Purnadianti, Mely (Universitas Muhammadiyah Sidoarjo, 2023)
Lead (Pb) is the main pollutant in the environment. Lead in fuel is an additive that is added to a gasoline mixture with the aim of increasing combustion so that vehicle performance increases. Lead is a type of heavy metal that can cause poisoning. Lead is easily absorbed in the body and can accumulate in human tissues. Lead can enter the human body through the respiratory system, orally, or through the skin surface. High lead levels in the blood can cause low platelets. This is because lead can interfere with the heme system in the blood, causing anemia. The aim of the study was to determine the relationship between lead (Pb) levels and blood platelet counts at gas stations in Mekikis Village. The research design in this study used a cross sectional approach. The research sample consisted of 10 gas station attendants. The sampling technique used was purposive sampling. Based on the examination, the average lead and platelet levels for gas station workers were 0.4344 ppm and 293,500 /UL respectively. Based on the results of the Spearman correlation test, a significant value of 0.391 was obtained where the sign value was > 0.05, which means that there is no relationship between lead levels and the number of platelets in the blood of Mekikis Village gas station attendants.